Ultrasound-assisted solid Lewis acid-catalyzed transesterification of Lesquerella fendleri oil for biodiesel synthesis - Mohammed Shahidul Islam; Cari Robin Hart; Dominick Casadonte (Ultrasonics Sonochemistry, 2022)
Biodiesel, a mixture of fatty acid methyl esters (FAME), is bio-renewable, non-toxic, biodegradable, and is an attractive alternative to petroleum diesel. This work studied the sonochemical transesterification of Lesquerella fendleri oil (LFO) using inexpensive solid Lewis acid (LA) catalysts with an aim to reduce environmental pollution and dependance on non-renewable fuel sources. Due to the presence of hydroxy fatty acid methyl esters (HFAME) in LFO (∼60%), in addition to producing biofuel it can also be used to generate chemically important estolides and cyclic lactones. AlCl3, SnCl2, and Sn(CH3COO)2 showed catalytic activity using direct immersion ultrasound (DI-US) among a list of LA catalysts investigated, with AlCl3 being the best catalyst. Ultrasound increased the reaction rate by facilitating carbocation formation of glyceridic carbons. Experiments were carried out at room temperature in a solvent range from 3:1 to 18:1 methanol-to-oil molar ratio and catalyst loading from 1 wt% to 6 wt% over 10 to 60 min sonication time at 48% ultrasound amplitude (roughly 17 W/cm2). Complete conversion (>99%) was achieved in 40 min with 5 wt% AlCl3 catalyst. A statistical regression analysis with STATA 14.0 software was performed to optimize process parameters. Chemical characterizations of the compounds were performed with nuclear magnetic resonance (NMR) spectroscopy (1H NMR & 13C NMR), and % conversion of FAMEs was calculated from the 1H NMR spectra. The fatty acid profile was determined by GC-FID and GC–MS analysis. FT-IR spectroscopic analysis and thermogravimetric analysis (TGA) were performed to investigate the infrared absorption pattern of the compound and the volatility difference between Lesquerella fendleri biodiesel and oil under nitrogen atmosphere. Results indicate that this is a fast, green, energy-efficient, sustainable, and industrially applicable method for biodiesel production from LFO.